![image](https://tex.z-dn.net/?f=1%29+%5Cfrac%7B4%7D%7B5%7D+x%5E%7B2%7D+%3D45+%3D%3E+x%5E%7B2%7D+%3D+%5Cfrac%7B45%2A5%7D%7B4%7D+%3D+%5Cfrac%7B225%7D%7B4%7D+%5C%5C+x_1%3D+%5Cfrac%7B15%7D%7B2%7D%3B+x_2%3D+-+%5Cfrac%7B15%7D%7B2%7D%3B+%5C%5C+%5C%5C+2%29+x%5E%7B2%7D+-24x%3D-22x%2B24-+x%5E%7B2%7D+%5C%5C+2+x%5E%7B2%7D+-2x-24%3D0+%5C%5C+x%5E%7B2%7D+-x-12%3D0+%5C%5C+D%3D1%2B4%2A12%3D49%3D7%5E2+%5C%5C+x_1%3D4%3Bx_2%3D-3+%5C%5C+%5C%5C+3%29-+x%5E%7B2%7D+%2B3x%2B55%3D%28x%2B7%29%5E2+%5C%5C+-+x%5E%7B2%7D+%2B3x%2B55%3D+x%5E%7B2%7D+%2B14x%2B49+%5C%5C+2+x%5E%7B2%7D+%2B11x-6%3D0+%5C%5C+D%3D11%5E2%2B4%2A2%2A6%3D169+%5C%5C+x_1%3D+%5Cfrac%7B-11-+13%7D%7B4%7D%3D-6+%3Bx_2%3D+%5Cfrac%7B-11%2B+13+%7D%7B4%7D%3D0%2C5)
x^{2} = \frac{45*5}{4} = \frac{225}{4} \\ x_1= \frac{15}{2}; x_2= - \frac{15}{2}; \\ \\ 2) x^{2} -24x=-22x+24- x^{2} \\ 2 x^{2} -2x-24=0 \\ x^{2} -x-12=0 \\ D=1+4*12=49=7^2 \\ x_1=4;x_2=-3 \\ \\ 3)- x^{2} +3x+55=(x+7)^2 \\ - x^{2} +3x+55= x^{2} +14x+49 \\ 2 x^{2} +11x-6=0 \\ D=11^2+4*2*6=169 \\ x_1= \frac{-11- 13}{4}=-6 ;x_2= \frac{-11+ 13 }{4}=0,5" alt="1) \frac{4}{5} x^{2} =45 => x^{2} = \frac{45*5}{4} = \frac{225}{4} \\ x_1= \frac{15}{2}; x_2= - \frac{15}{2}; \\ \\ 2) x^{2} -24x=-22x+24- x^{2} \\ 2 x^{2} -2x-24=0 \\ x^{2} -x-12=0 \\ D=1+4*12=49=7^2 \\ x_1=4;x_2=-3 \\ \\ 3)- x^{2} +3x+55=(x+7)^2 \\ - x^{2} +3x+55= x^{2} +14x+49 \\ 2 x^{2} +11x-6=0 \\ D=11^2+4*2*6=169 \\ x_1= \frac{-11- 13}{4}=-6 ;x_2= \frac{-11+ 13 }{4}=0,5" align="absmiddle" class="latex-formula">